Health-Related Quality of Life and the Prevalence of Post-Traumatic Stress Disorder among Crimean-Congo Hemorrhagic Fever Survivors - (:unkn) unknown (NATL INST INFECTIOUS DISEASES, 2012)
Crimean-Congo hemorrhagic fever (CCHF) is a potentially fatal infectious disease, and it is endemic in Turkey. Patients are placed in isolation when hospitalized, and some may require blood transfusions. Moreover, some patients may require admission to intensive care units (ICU). CCHF is not a recurrent disease, and relapses are not expected. Therefore, no medical follow-up is conducted on recovery from CCHF. In this study, health-related quality of life (HRQL) and the presence of post-traumatic stress disorder (PTSD) among CCHF survivors were evaluated 12 months after recovery from the disease. PTSD diagnosis was established by DSM-IV-TR criteria and HRQL was investigated by using the Medical Outcomes Study Short Form 36. This study included 54 patients. Our results showed that 48.1% of the patients had PTSD symptoms and 18.5% had PTSD. PTSD incidence was higher among patients who required an ICU stay, who had bleeding, and who required blood transfusion. In addition, 4 out of 8 dimensions of HRQL were impaired. However, none of these patients admitted psychiatric problems to health care professionals. Our findings revealed that periodic psychiatric evaluation should be performed on CCHF patients, and they should be provided medical support, if required.
Keywords: SARS SURVIVORS; OUTBREAK; DISEASE; TORONTO